The Effect of Giving the Combined Liquid Organic Fertilizer of Gamal Leaves (Gliricidia sepium) and Kepok Banana Peel (Musa Paradisiaca) on the Growth and Yield of Paprika (Capsicum annum var. Grossum) - Indrawati Wijayakusuma; Theodora Maasawet; Didimus Tanah Boleng (Nabatia, 2023)
This study aims to examine the growth and production of paprika (Capsicum annum var. Grossum) when treated with liquid organic fertilizer mixed with gamal leaves and kepok banana peels, and to recommend the optimal dose for this treatment. Plantation land on Jalan Maridan Riko in Maridan Village, Sepaku District, North Penajam Paser District, East Kalimantan was surveyed for this study. Five different doses, labeled P0 (Control), P1 (40 ml), P2 (80 ml), P3 (120 ml), and P4 (160 ml), were tested in a randomized block design trial. Plant height among the measured variables, number of leaves, number of fruits, fruit weight. Based on the results of analysis of plant height growth data Fcount (6.88) > Ftable (2.87), analysis of data on the number of plant leaves Fcount (60.92) > Ftable (2.87), analysis of data on the number of fruit Fcount (6.66) > Ftable (3.02) and results of fruit weight data analysis Fcount (2.91) > Ftable (2.87). These findings indicate that the optimal dose of liquid organic fertilizer for gamal leaves and kepok banana peels is 120 ml (P3), and this has a real impact on the development and yield of chili (Capsicum annum var. Grossum).